2019
DOI: 10.3349/ymj.2019.60.8.727
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA MALAT1 Regulates Hepatocellular Carcinoma Growth Under Hypoxia via Sponging MicroRNA-200a

Abstract: Purpose Hepatocellular carcinoma (HCC) is a common cancer worldwide. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), a long noncoding RNA (lncRNA), has been reported to be aberrantly expressed in hypoxic cancer cells. MALAT1 plays a significant role in many malignancies, including HCC. The aim of this study was to explore the role of MALAT1 in hypoxic HCC cells and its underlying regulatory mechanism. Materials and Methods Quantitative reverse transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…25 Miao et al reported that lncRNA ANRIL changed the sensitivity of OC cells to DDP by mediating let-7a and HMGA2 levels. 26 LncRNA linc00312 regulated DDP resistance of OC cells via modulating Bcl-2/Caspase-3 pathway. 27 Therefore, lncRNAs exerted the crucial function in DDP-resistant OC cells.…”
Section: Discussionmentioning
confidence: 99%
“…25 Miao et al reported that lncRNA ANRIL changed the sensitivity of OC cells to DDP by mediating let-7a and HMGA2 levels. 26 LncRNA linc00312 regulated DDP resistance of OC cells via modulating Bcl-2/Caspase-3 pathway. 27 Therefore, lncRNAs exerted the crucial function in DDP-resistant OC cells.…”
Section: Discussionmentioning
confidence: 99%
“…29 Hypoxia, which plays an important role in solid tumor development, can enhance MALAT-1 expression in HCC. 24,30 MALAT-1 was shown to modulate the proliferation, apoptosis, migration, and invasion HCC cells exposed to hypoxia by sponging miR-200a. 24 MALAT-1 indirectly activates Sirt1 deacetylase by competing for binding with Depleted in breast cancer (DBC)1; this ultimately results in the deacetylation of p53, which inhibits proapoptosis gene expression and promotes tumor cell growth.…”
Section: Malat-1 In Cancer Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Several functional studies on miR-200a have been conducted in vertebrates. In human and mice, it was reported that MALAT1 affected proliferation, migration, invasion, and apoptosis during the progression of hypoxic hepatocellular carcinoma by sponging miR-200a [11]. Moreover, miR-200a mediated the proliferation of hepatic stellate cells and development of fibrosis by targeting the 3′-UTR of SIRT1 via the SIRT1/Notch signal pathway [12].…”
Section: Introductionmentioning
confidence: 99%